IPTEKS AKUNTANSI SUMBER DAYA MANUSIA PADA PENCAPAIAN TARGET CONSUMER LOAN - Johannes, Christy Handayanie; Kindangen, Wulan D. (Universitas Sam Ratulangi, 2018)
Human Resources are important assets, Accounting for human resources Human Resource Accounting is an acknowledgment that people constitute human capital and human assets. The economic theory of human capital is based on the concept that humans have the skills, experience, and knowledge which are forms of capital, which are called